Rhamnolipids Regulate Lipid Metabolism, Immune Response, and Gut Microbiota in Rats - Zhang, Bing; Qin, Songke; Wu, Yanping; Zhang, Ruiqiang; Xu, Yinglei; Yang, Caimei (Frontiers in Nutrition, 2022)
Objectives: Gut microbes influence lipid metabolism and immune responses that are key features of metabolic disorders. This study examined effects of bacterial rhamnolipids (RLS) on lipid metabolism, immune response, and gut microbiota in rats. Methods: Twenty-four Sprague-Dawley rats were randomly divided into three groups and gavage-fed for seven weeks with normal saline (NCO group), 50 mg/kg bw RLS (RLS1 group), and 100 mg/kg bw RLS (RLS2 group). Results: Compared with those of the NCO group, the RLS1 and RLS2 groups showed significantly decreased fat weight, relative fat weight, and adipocyte size (P < 0.05). Furthermore, RLS1 and RLS2 significantly decreased concentrations of triglycerides, low-density lipoprotein-cholesterol, and non-esterified fatty acids and increased high-density lipoprotein-cholesterol levels (P < 0.05). However, the total cholesterol content among the three groups (P > 0.05) were not significantly different. Serum concentrations of interleukin-1β, interleukin-6, and TNF-α were significantly lower in the RLS2 group than those in the NCO group (P < 0.05). The relative mRNA expression of fatty acid synthase was significantly decreased, while those of carnitine palmitoyltransferase-1, carnitine palmitoyltransferase-2, and peroxisome proliferator-activated receptor-gamma coactivator-1α were significantly increased in the RLS2 group compared with those in the NCO group (P < 0.05). Moreover, the relative abundances of Lactobacillus, Roseburia, Ruminococcus-1, and Parabacteroides were significantly higher in the RLS2 group than those in the NCO group (P < 0.05). Conclusion: Our findings suggest that RLS reduces fat deposition, inhibits inflammation, regulates intestinal flora, and promotes the proliferation of beneficial bacteria in rats.